Self-Assembly of Oriented Antibody-Decorated Metal-Organic Framework Nanocrystals for Active-Targeting Applications - Alt, Karen (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2021 The Authors. Advanced Materials published by Wiley-VCH GmbH.